PEMETAAN KELURUSAN MENGGUNAKAN REMOTE SENSING DAN KORELASINYA TERHADAP DISTRIBUSI MANIFESTASI PERMUKAAN DI DAERAH POTENSI GEOTHERMAL KEPAHIANG, BENGKULU - Herlambang, Ricky Ferdianto; Novranza, Kms (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The application of remote sensing technology has currently evolved and covering a wide scope of study, for instance in geothermal exploration. Remote sensing can help identify the geological structures on the surface through observation of lineament features. The geological structures in geothermal exploration are related to permeable zones and can be correlated with the upflow or outflow zone as indicated by the presence of surface manifestations. Landsat-8 imagery is used in delineating the lineament as in advanced, the process was begun by doing image quality enhancement Gram-Schimdt Pan-Sharpening and PCA (Principal Component Analysis). Extraction of lineaments process was carried out with LINE module of PCI-Geomatica based on automatic detection algorithms. To reduce lineament features that are not related to the geological structure, such as man-made features, visual observation is conducted by using several band combinations. The results showed that the main direction of the lineaments within the study area is Northwest-Southeast, consistent to the pattern of major geological structures in Regional Geological Map and related to the existence of manifestations. However, from the observation of Lineament Density Map, there were no direct correlations between areas that have a high density of lineaments with the presence of surface manifestations. Lineament density tends to be dominantly influenced by the geological formation. Keywords: Remote sensing, Landsat-8, Lineament, Geothermal, Surface Manifestations.